2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.25
|View full text |Cite
|
Sign up to set email alerts
|

A New Way to Plan for the Future

Abstract: Abstr actBuilding on state-of-the-art techniques for forecasting future developments in technology, business, economics, and other areas of human endeavor, we describe a novel methodology for adaptive contingency planning at the strategic initiative level. Complementing normal business planning that uses a schedule based on predictions tied to dates in the future, we use a new kind of early warning signal called a signpost to trigger the execution of corresponding new recommended actions. Intr oductionA signpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…IBM does not recommend that the client work to create the breakthroughs because they are so massive that even the most capable client would contribute little to their occurrence. What is more, breakthroughs are by definition unpredictable, particularly when they will occur, so that they recommend rather that the client monitor for the occurrence of the breakthrough and then deploy a contingent strategy during a subsequent window of opportunity for exploiting the capabilities of the breakthrough (see Strong, 2006). Future mapping .…”
Section: Scenario Techniquesmentioning
confidence: 99%
“…IBM does not recommend that the client work to create the breakthroughs because they are so massive that even the most capable client would contribute little to their occurrence. What is more, breakthroughs are by definition unpredictable, particularly when they will occur, so that they recommend rather that the client monitor for the occurrence of the breakthrough and then deploy a contingent strategy during a subsequent window of opportunity for exploiting the capabilities of the breakthrough (see Strong, 2006). Future mapping .…”
Section: Scenario Techniquesmentioning
confidence: 99%
“…Define milestones and interim objectives. Strong et al (2007) suggested that the key element for constructing the pathway back from the future involves the identification of signposts. They define a signpost as a "recognizable potential future event that signals a significant change."…”
Section: Methodsmentioning
confidence: 99%
“…Normative-based approaches, even those that do include a visioning process, such as backcast modeling [16,17], future mapping [18], horizon mission methodology [19], the impact of future technologies scenarios [20] and sociovision [21], do not explicitly model the future desirable state. Instead, sets of goals, moving targets or indicators representing the vision are generally used to direct and assess scenario pathways.…”
Section: Sustainability Modeling and Current Applicationsmentioning
confidence: 99%